Substantiation of Parameters of the Network Model of the Air Distribution Due the Piston Effect in the Extra-Long Tunnels - Aleksandr Krasyuk; Ivan Lugin; Tuleukhan Irgibayev; Elena Alferova (Applied Sciences, 2023)
The article analyzes the aerodynamic processes initiated by the piston effect in extra-long railway tunnels. The authors numerically modelled the movement of a freight train, 1 km long, in tunnels 3 and 6 km long. The analysis used the ANSYS Fluent environment. The modeling determined the air pressure at the front and back faces of the train, the draught loss in the tunnel clearance, as well as the air velocity in the tunnel clearance and in the tunnel. These data are used to develop a quasi-dynamic model of the piston effect for solving problems concerning air distribution with the application of network models. The air flow rates calculated in ANSYS Fluent and using the network models agree quite well. The time of the problem solving for a tunnel 3 km long using the network model is shorter by 5 orders of magnitude, which is of significant importance for both the study and multivariate design of ventilations systems for railway tunnels.